Acedia and David Foster Wallace’s The Pale King - Zuzanna Ladyga (European Journal of American Studies)
The article makes the case for David Foster Wallace’s The Pale King as a literary intervention into the American ethos of productivity, which offers a critique of this ethos by exploiting the trope of acedia, or boredom. Wallace’s novel employs acedia as the mode of its subjectivity and its main theme, thus creating a unique, recursive aesthetics, which is resistant to “productive” interpretations. Following Wallace’s own vocabulary, I call this aesthetics “the aesthetics of the feedback glare.” As a result of its recursive dynamics, the novel creates a series of micro-events. They can be classified as what Lauren Berlant calls “self-interruptions”: the events that guard the heterotopic territory of the subject’s (as well as the author’s) agency against interpellative calls of the book industry for self-exploitation and productivity.